Cover Picture: Phys. Status Solidi C 9/2013. Issue 9 (9th September 2013) - Ulrich, Sven M.; Jetter, Michael; Michler, Peter
<x xml:space="preserve">Abstract</x> The interest in the optical control of exciton states in a quantum dot (QD) has been stimulated by recent experiments, where the QD was controlled either by means of Rabi oscillations or by using chirped laser pulses exploiting the adiabatic rapid passage (ARP). On pp. 1210–1213, Gawarecki and coworkers investigate the exciton dynamics in a quantum dot adiabatically controlled by a frequency‐swept (chirped), linearly polarized laser pulse in the presence of carrier–phonon coupling. The final occupation of the exciton state is limited both due to phonon‐induced transitions between the adiabatic spectral branches and because of phonon‐assisted transitions to the biexciton state. When the biexciton shift is large enough, the quantum dot can be modeled as a two‐level system, which corresponds to excitation with circularly polarized light. For this case the authors compare the results obtained from three different simulation methods, namely time‐convolutionless method (TCL), correlation expansion (CE) and path integrals (PI). The results obtained from CE and PI show very good agreement, even at T = 50 K. The TCL agrees perfectly with the other two methods at low temperatures and agrees reasonably at moderate temperatures, but at high temperatures a mismatch of up to 30% was found. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>